An extended framework for science. (December 2017) - Cazalis, Roland
Abstract: We may be at the cusp of a next generation framework for science which can be facilitated by understanding current limitations in the context of a divergence of 'scientific' tradition from the Axial Age (800–200 BCE) to the present. A powerful advance may come from fusing certain elements from Western and Eastern traditions, synthesizing the framework with an apt understanding of the divergence. Key traits will include the ethopoetic nature of the scientist with attention to his/her experience of self. The framework will also 'access' knowledge through a state of mind less encumbered with paradoxes, duality, incompatibility and other aporias. Case studies in biology and physics illustrate possibilities.